2016
DOI: 10.1002/jqs.2845
|View full text |Cite
|
Sign up to set email alerts
|

A diatom‐inferred record of lake variability during the last 900 years in Lützow–Holm Bay, East Antarctica

Abstract: Decadal-centennial-scale climate variability in coastal Antarctica remains poorly understood due to the limited number of highly resolved, well-dated records. We present a 900-year, decadal-scale reconstruction based on sedimentary diatoms from Lake Abi in L€ utzow-Holm Bay, East Antarctica. Hydrological change is inferred from diatom ecological preferences in conjunction with an existing regional training set and implies that lake water specific conductivity, depth and nitrogen availability are the key driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Ideally, an even gradient of lake chemical and physical characteristics would be studied, but this is limited by the types of lakes present in the landscape, and by field logistics. This means that for some species this study is unable to shed much light on chemical or habitat preferences, including C. antarctica , which is a common diatom taxon in lake sediment diatom records in the region (e.g., Rudd et al, 2016; Tavernier et al, 2014). Craticula antarctica was most abundant in the benthic lake‐floor samples from Lakes Kuwai and Hotoke in this study and was not observed at Lake Nurume.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ideally, an even gradient of lake chemical and physical characteristics would be studied, but this is limited by the types of lakes present in the landscape, and by field logistics. This means that for some species this study is unable to shed much light on chemical or habitat preferences, including C. antarctica , which is a common diatom taxon in lake sediment diatom records in the region (e.g., Rudd et al, 2016; Tavernier et al, 2014). Craticula antarctica was most abundant in the benthic lake‐floor samples from Lakes Kuwai and Hotoke in this study and was not observed at Lake Nurume.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of light in the shallow littoral zone of Antarctic lakes can be a physical stressor influencing assemblage differences (Hughes et al, 2006; Tanabe et al, 2008), which may, in combination with the low nutrient availability on rock surfaces in the shallow littoral zone, result in the lower proportional representation of littoral diatoms in deeper sediments. The clear distinction between littoral and lake‐floor diatom assemblages across the nine lakes studied, and the presence of diatom species commonly associated with littoral habitats within lake core samples (Rudd et al, 2016) consequently suggests that there is potential to qualitatively infer changes in lake ice cover from the ratio of littoral to lake‐floor of sedimentary diatoms in Lützow‐Holm Bay lakes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations